How websites compete in the Middle East: The example of Iran. Issue 1 (28th October 2021) - Naami, Tara; Anesbury, Zachary William; Stocchi, Lara; Winchester, Maxwell
Abstract: Based on the analysis of two sets of data (a cross‐sectional online survey of five product categories with an average sample size of 525 and a longitudinal telecommunications panel of more than two million respondents), this study detects a positive relationship between the market size (purchase penetration) of Iranian e‐brands (or websites) and the percentage of customers shared with other e‐brands. This finding is consistent with the well‐established Duplication of Purchase Law; it also holds over time and across different markets (e.g., repertoire vs. subscription). Hence, this study makes a twofold contribution to marketing knowledge. First, it expands the collection of empirical evidence concerning the Duplication of Purchase, which thus far is primarily within offline contexts and Western countries. Second, it addresses issues inherent to research on e‐loyalty, such as the over emphasis on evaluating loyalty for one e‐brand at a time via complex attitudinal measures. Accordingly, this study advances consumer buying behaviour research by clarifying that, similar to offline domains and other geographical areas, e‐loyalty in this buoyant Middle Eastern market divides across a small number of e‐brands. It is also best appraised through behavioural loyalty and by comparing multiple e‐brands competing within the same market. These outcomes translate into a series of practical guidelines for the strategic management of e‐brands, improving the practical understanding how e‐brands compete and grow.